Clinical profile of tuberculosis with diabetes mellitus - Gautam, Pooja; Sharma, Neelima; Gautam, Bishal; Sharma, Preksha; Sharma, Neha (International Journal of Research in Medical Sciences, 2021)
Background: There is now good evidence that people with diabetes mellitus (DM) have 2–3 times the risk of developing active tuberculosis (TB) compared with those who do not have DM. The aim of the study was to analyze typical / atypical presentation of pulmonary tuberculosis with diabetes mellitus. Methods: This study was carried out in the Department of Respiratory Medicine and General Medicine, SAIMS, Indore during the period of July 2012 to June 2014. A prospective study including 100 microscopically proven cases of sputum smear positive pulmonary tuberculosis. Among these, 50 are diabetic patients with sputum positive tuberculosis and 50 are non-diabetic patients with sputum positive tuberculosis. Results: The mean age in diabetic group was 51.92±9.96 years. The mean age in non-diabetic group was 39.58±15.19 years. In the diabetic group, there were 38 (76.00%) male and 12 (24.00%) females, while in the non-diabetic group there were 40 (80.00%) males and 10 (20.00%) females. Fever, cough and weakness were the three most common symptoms seen in patients with tuberculosis in both the groups. Conclusions: There was a preponderance of male in both the groups over the female patients. There is no significant difference in the symptoms in both the groups.